Stressors and Coping Strategies as Perceived among Nursing Students during Related Learning Experience (RLE) - Ridad, Geraldine Sabate; Angintaopan, Haniya; Ayunan, Princess Haniefa Mae; Manalocon, Saipoden (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Stress in relation to academic studies is identified to be one of the reasons behind suicide cases in higher education institutions around the world. Locally, there is none to less studies that explored this area among nursing students. As stress is inevitable in nursing students’ Related Learning Experience (RLE), recognizing the stressors that affect their quality of RLE is necessary.Purpose: This study aimed to investigate the stressors and coping strategies that nursing students commonly use in managing stress during their RLE and their relationship to each other.Methods: A descriptive correlational research design with total enumeration sampling was employed. A pilot-tested questionnaire was used to gather data from 191 junior and senior nursing students from two nursing schools in Iligan City. Weighted mean, standard deviation, percentages, and Spearman rho were used to analyze the data.Results: The findings show that the